APPROACHES TO THE INTRODUCTION OF THE CONCEPT INDUSTRY 4.0. AMERICAN AND GERMAN PLATFORMS - K. Mukhin; Y. Antokhina (Вестник Северо-Кавказского федерального университета, 2022)
The modern world is at the stage of the fourth industrial revolution, called Industry 4.0. Given the high, fundamental importance of digital technologies, software, and the complementary work of complex systems, the emergence of platforms to ensure the effective operation of these processes has become inevitable. To date, there are two main approaches, two main platforms that meet the requirements of the new production paradigm, German RAMI Industry 4.0 and the American IIRA Industrial Internet Consortium (Industrial Internet Consortium). These platforms advocate seemingly different conceptual conditions that are reflected, on the one hand, in the careful observance of standards, and on the other hand, following innovative, free ideas in realizing the principles of Industry 4.0 in practice. Regarding the procedures that must be followed for future production and the Internet of things, the differences between approaches in Germany and the US may not be noticeable, but they definitely are. Two conceptual approaches and two diferent architecture of building processes at this stage of the fourth industrial revolution afect the development of all technological development. In this article, we analyzed the relationship of these platforms with each other in terms of technological development in general.